PEMBELAJARAN MEMBACA ANAK USIA DINI BERBASIS TEKNOLOGI INFORMASI - Yulsyofriend Yulsyofriend (Pedagogi: Jurnal Ilmu Pendidikan, 2013)
Aspects of early childhood development can be stimulated to provide interesting learning activities and method of multi-media . The research was conducted in FY Pertiwi Limaumanis Padang VI seeks to determine level of reading development as one part of the learning aspects of language development through multi-media computer . Learning to read children stimulated with software compact disc reading program . Use research methods class room with two action research cycles, each cycle of three meetings . Results of this study show the effectiveness of the development of children with significant reading shown by the results of data analysis increase child reading a good attitude and good once 92.5 % . Increase the child read well and good 87.5 % . This generally means that the expansion of learning to read children have reached a minimum completeness criteria ( MOH). Therefore this assessment cycle II halted until 4 meeting , because minimal consistency in the development of learning to read children reached.